The Upper Triassic Chedabucto Formation, Guysborough County, Nova Scotia: depositional and tectonic context - Tanner, Lawrence; Brown, David (Atlantic Geology, 1999)
The Chedabucto Formation of presumed Late Triassic age crops out at the western end of the Orpheus basin. The formation consists of interbedded conglomerate, sandstone, and mudstone interpreted as the deposits of sand-dominated braided streams, and clast-supported conglomerate interpreted as debris-flow deposits derived from nearby fault talus. The facies and presumed age of the Chedabucto Formation are similar to that of the Wolfville Formation in the Minas subbasin of the Fundy rift basin. These facies may also be present in the lower portion of the Eurydice Formation at the base of the sedimentary section in the offshore Orpheus basin. The location of the outcrops of the Chedabucto Formation suggests that a continuous belt of sedimentation connected the Orpheus and Fundy rift basins in the Late Triassic, forming a "broad terrane" extending from eastern New Brunswick to the Scotian Shelf. The Chedabucto Formation was deposited primarily by an axial river system flowing eastward from the Fundy rift basin to the Orpheus basin. The Minas subbasin of the Fundy rift basin and the Orpheus basin are interpreted as segments of a larger transtensional basin formed by synchronous oblique-sinistral motion on the bounding Cobequid-Chedabucto Fault Basin inversion in the Middle Jurassic probably initiated uplift, resulting in the erosional isolation of the Fundy and Orpheus basins.